Endocrine Disrupting Chemicals and Human Health: A Review of Toxicological Mechanisms and Regulatory Challenges - Mona M. Youssef; Aya M. Helal; Yasser I. Khedr (Journal of Biomedicine and Biochemistry, 2025)
The present review is to evaluate the current state of knowledge in regard to health effects of endocrine disrupting chemicals (EDCs) in humans, with a special reference to recently published research. The primary target audi- ence aside from scientists will be policymakers, public health professionals, and health practitioners who need an up-to-date broad understanding of the issue in the form of a concise compilation of peer-reviewed literature. The main goal serves to synthesize recent research findings regarding the most important toxicological mechanisms associated with EDCs and recent advancements in understanding their health effects. A major emphasis is placed on research that has been published in peer-reviewed journals over the past years, with less attention being given to systematic reviews. Infor- mation found in the literature bears a description of current knowledge of the human health effects of EDCs, focusing on recent scientific publications. Greater familiarity with the complexities of EDC exposure routes, mech- anisms, and the large variety of chemicals that have endocrine-disrupting properties is also aimed. By detailing the state of research, it is hoped that the review may help clarify the complexities for regulatory authorities, enabling for more accurate decision-making with regards to management of EDCs. Additionally, this contribution is intended to advance the cur- rent public health and regulatory debate about EDCs, by highlighting the challenges faced in regulation and proposing potential directions for their effective management.